1977
DOI: 10.3181/00379727-154-39690
|View full text |Cite
|
Sign up to set email alerts
|

Role of Bovine Serum Albumin in Blastoid Transformation of Lymphocytes by Phytohemagglutinin

Abstract: Human peripheral lymphocytes are activated to. undergo blast transformation by specific and nonspecific stimulants in vitro (1)(2)(3). Supplementation with autologous serum or fetal calf serum to the medium is generally required for the transformation of lymphocytes. However, the factor(s) in serum which cause blast transformation of the stimulated lymphocytes are still unknown.The study of such factors in serum may reveal the mechanism of activation and proliferation of the stimulated lymphocytes. Polet and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

1982
1982
1994
1994

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 2 publications
2
14
0
Order By: Relevance
“…Previously, Uittenbogaart et al (24) reported failure to maintain long-term, serum-free cultures of Mo cells, which may have been due to the use of different supplements in the serum-free medium : They used delipidated BSA and did not add lipids and insulin. Lipids in particular, appear to be essential for the growth of Mo cell because we previously demonstrated the essential role of albumin-bound lipids in human T lymphocyte growth (1). Cohn frantion V BSA recently has been reported to be required for mouse erythropoietic burst production in vitro (19) and the same authors speculated that Cohn fraction V BSA might facilitate the production of burst-promoting activity by bone marrow T cells (19).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Uittenbogaart et al (24) reported failure to maintain long-term, serum-free cultures of Mo cells, which may have been due to the use of different supplements in the serum-free medium : They used delipidated BSA and did not add lipids and insulin. Lipids in particular, appear to be essential for the growth of Mo cell because we previously demonstrated the essential role of albumin-bound lipids in human T lymphocyte growth (1). Cohn frantion V BSA recently has been reported to be required for mouse erythropoietic burst production in vitro (19) and the same authors speculated that Cohn fraction V BSA might facilitate the production of burst-promoting activity by bone marrow T cells (19).…”
Section: Resultsmentioning
confidence: 99%
“…circumvent these problems when culturing human lymphoid (1,3,4,15,17,21,24), erythroleukemic (14,23), promyelocytic (2,20) and murine lymphoid (11,13) cell lines as well as murine bone marrow cells (6,10,12,19). We previously reported the development of a serum-free medium which supports the growth of human B lymphocytes that are stimulated by pokeweed mitogen to produce immunoglobulines (21).…”
mentioning
confidence: 99%
“…In addition to 0.5% BSA (Sigma Chemical Co., St. Louis, Mo. ), Eagle's minimum essential medium (MEM) was supplemented with sodium pyruvate, insulin, putrescine, zinc sulfate and various nucleosides, as described previously (Yamane et al 1976; Arai et al 1977). RPMI 1640 with 10% heat-inactivated fetal calf serum (FCS; Grand Island Biological Co., Grand Island, N.Y.) was used as serum containing medium.…”
Section: Methodsmentioning
confidence: 99%
“…The cells (5 X 105/ml) were incubated in microplates (Falcon 3040) in serum-free medium (Arai et al 1977) with or without PHA-P(Difco) and saccharated ferric oxide (`Fesin', Yoshitomi Pharmaceut.…”
Section: Methodsmentioning
confidence: 99%
“…In the course of our investigation of the factors supporting lymphocyte growth in serum-free medium (Arai et al 1977), we found that saccharated ferric oxide enhanced the [3H]thymidine incorporation into the phytohemagglutinin (PHA)-stimulated lymphocytes in serum-free culture medium supplemented with bovine serum albumin and insulin.…”
mentioning
confidence: 99%